2014
DOI: 10.1088/0268-1242/29/11/115032
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of the operation of GaN planar nanodiodes as sub-THz emitters in resonant circuits

Abstract: A study of the high-frequency performance of GaN-based asymmetric self-switching diodes (SSDs) designed for a room-temperature sub-THz Gunn emission, and connected to a resonant RLC parallel circuit, is reported. With the aim of facilitating the achievement and control of Gunn oscillations, which can potentially allow the emission of THz radiation by GaN SSDs, a time-domain Monte Carlo (MC) theoretical study is provided. The simulator has been validated by comparison with the I-V curves of similar fabricated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…New devices called self-switching diodes have been proposed as promising candidates to exhibit high-frequency GOs in the sub-THz range [16,17]. Focusing the electric field by shaping the profile of nanochannels, they should be able to improve the efficiency of planar Gunn diodes and even help to achieve the challenging fabrication of GaN Gunn diodes [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…New devices called self-switching diodes have been proposed as promising candidates to exhibit high-frequency GOs in the sub-THz range [16,17]. Focusing the electric field by shaping the profile of nanochannels, they should be able to improve the efficiency of planar Gunn diodes and even help to achieve the challenging fabrication of GaN Gunn diodes [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The particular symmetry of the I-V curve in the V-shaped geometry results in a Gaussian-like curve of R V , has stimulated investigations in Gunn oscillations-based devices, since it has been demonstrated that this type of electrical oscillations in SSDs could reach submillimeter wavelengths. [21][22][23] Millithaler et al concluded that the V-shaped geometry needs a lower DC current to generate Gunn oscillations, improving the DC-to-AC efficiency and reducing the thermal dissipation issues when compared to L-shaped devices. 22) However, in their design, the diode-like curve is poor due to the large channel width.…”
Section: I-v Characteristics Analysismentioning
confidence: 99%
“…Remarkably, in GaN SSDs, the strategic combination of the SSD geometry with the presence of negative differential mobility, high electrical strength, high saturation velocity and low energy relaxation time, offers an optimal environment for the generation of very high frequency Gunn oscillations [11]. However, in spite of the efforts made in recent years [12,13], no clear experimental evidence of THz oscillations was found so far in GaN manufactured devices. In any case, the good performances of GaN SSDs as detectors of submillimeter-wave signals [14] combined with their planar geometry, which allows for a better free space coupling and a flexibility in the design (for an optimum thermal dissipation and reduction of parasitic effects), enables them to operate not only as detectors but also opens the possibility to develop a completely integrated emitter/detector submillimeter-wave working at room temperature and motivates our study of the behavior of traps in GaN SSDs.…”
Section: Introductionmentioning
confidence: 99%